Upaya Meningkatkan Hasil Belajar Siswa Dalam Memahami Qowaid Ilmu Nahwu Dengan Menggunakan Media Rumus Arab Pegon - Dede Rizal Munir; Abdul Rahmat Fauzi (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research aims to find out: 1). The use of the Arabic pegon formula media is able to increase students' learning activity in understanding the qowaid of nahwu science at MDTA Fathun-Najah. 2). The use of the Arabic pegon formula is able to improve student learning outcomes at MDTA Fathun-Najah in understanding the qowaid science of nahwu. The research carried out in this study was a classroom action research consisting of three action cycles. Data collection techniques through observation, tests and documentation. The results of the research show that the use of the Arabic Pegon formula media is able to increase students' learning activity in understanding the Qowai'd of Nahwu science and students who learn using the Arabic Pegon formula experience a significant increase in their ability to master the Qowai'd of Nahwu science. This research also has an important impression for educators and instructors in the MDTA environment or similar educational institutions. Teachers can consider using the Arabic Pegon formula as a learning tool that can help students understand and master Qowai'd Ilmu Nahwu better.